Educating Young Learners in English: A Review of the Literature (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study looked at engaging teaching strategies that encourage student engagement and language acquisition, age-appropriate English teaching resources, and the value of fostering a positive learning environment for young learners. This study employs the library research approach, which entails seeking and identifying sources of factual data or firsthand or expert commentary on a research subject. This method's ability to improve performance is why it was selected for this investigation. As a result, this study's premise needs solid theoretical and experimental backing. Studies on young learners' age-appropriate English teaching resources demonstrate the efficacy of various approaches. In order to engage younger kids, research emphasizes the use of visual and interactive materials, storybooks, songs and hymns, games, and technological integration. These teaching strategies not only hold students' interest but also advance their language proficiency, understanding, and vocabulary growth. They also include creating a secure space for communication, a supportive teacher-student connection, clear expectations and routines, collaborative learning, and a pleasant and encouraging environment. components need to provide the best possible learning. One cannot stress how crucial it is to build strong relationships between teachers and students since these ties are the cornerstone of a self-assured and supportive learning environment. The study also emphasizes the need of individualized instruction that takes into account the various learning preferences, language proficiency levels, and interests of young students. Teachers may make sure that every student feels appreciated and supported throughout their language learning process by customizing lessons to meet each student's requirements.